Letter (copy) : International Solidarity Fund: help for Spain - Tewson, Vincent
030-0100-001 Secretary's. HVT/FC/575 6th August, 1938. Mr. Ridley, The Railway Clerks' Association, 25, Euston Road, N.W.1. Dear Mr. Ridley, INTERNATIONAL SOLIDARITY FUND - HELP FOR SPAIN With reference to your telephone message of yesterday I have pleasure in enclosing information regarding the work of the International Solidarity Fund which I trust will be helpful to you. Yours sincerely, Assistant Secretary. 292/946/30/100